Prediction of energy efficient pedal forces in cycling using musculoskeletal simulation models - Höchtl, F.; Böhm, H.; Senner, V. (Procedia Engineering, 2010)
A biomechanical simulation model was developed to analyze energy efficient pedal forces in cycling. With a genetic optimisation algorithm muscle activation has been optimized in order to minimize metabolic energy consumption. Results show that the established mechanical definition of the Index of Efficiency is not appropriate to quantify pedaling technique, because it is not in agreement with metabolic efficiency of the biomechanical system.